2011
DOI: 10.1371/journal.pone.0024394
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Antibacterial Effects of Statins - In Vitro and In Vivo

Abstract: BackgroundStatin treatment has been associated with a beneficial outcome on respiratory tract infections. In addition, previous in vitro and in vivo experiments have indicated favorable effects of statins in bacterial infections.AimThe aim of the present study was to elucidate possible antibacterial effects of statins against primary pathogens of the respiratory tract.MethodsMIC-values for simvastatin, fluvastatin and pravastatin against S. pneumoniae, M. catarrhalis and H. influenzae were determined by tradit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0
12

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 19 publications
4
75
0
12
Order By: Relevance
“…Simvastatin and lovastatin (10 mg/liter) are also reportedly bactericidal against the spirochete Borrelia burgdorferi (the causative agent of Lyme disease) (45), and atorvastatin, rosuvastatin, and simvastatin were found to inhibit the growth of Escherichia coli, a prominent cause of gastroenteritis and urinary tract infections (38). In contrast, however, Bergman et al, using a maximum concentration of 250 mg/liter, observed that simvastatin did not inhibit the growth of H. influenzae (43), while Graziano et al found that simvastatin, atorvastatin, and pravastatin at concentrations up to 250 mg/liter did not inhibit the growth of P. aeruginosa, E. coli, or Enterococcus faecalis (42). Furthermore, a study by Thangamani et al (41) indicated that, while the growth of Gram- (41,42), it is worth noting that the E. coli ATCC 3218 assays were performed on solid agar while the other studies were performed using the broth microdilution method, perhaps explaining the apparent differences in activity.…”
Section: Effects Of Statins On In Vitro Bacterial Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…Simvastatin and lovastatin (10 mg/liter) are also reportedly bactericidal against the spirochete Borrelia burgdorferi (the causative agent of Lyme disease) (45), and atorvastatin, rosuvastatin, and simvastatin were found to inhibit the growth of Escherichia coli, a prominent cause of gastroenteritis and urinary tract infections (38). In contrast, however, Bergman et al, using a maximum concentration of 250 mg/liter, observed that simvastatin did not inhibit the growth of H. influenzae (43), while Graziano et al found that simvastatin, atorvastatin, and pravastatin at concentrations up to 250 mg/liter did not inhibit the growth of P. aeruginosa, E. coli, or Enterococcus faecalis (42). Furthermore, a study by Thangamani et al (41) indicated that, while the growth of Gram- (41,42), it is worth noting that the E. coli ATCC 3218 assays were performed on solid agar while the other studies were performed using the broth microdilution method, perhaps explaining the apparent differences in activity.…”
Section: Effects Of Statins On In Vitro Bacterial Growthmentioning
confidence: 99%
“…Taken together, the data suggest that the antibacterial activity of statins may be statin specific and/or strain/species specific or both. Simvastatin and atorvastatin generally appear to be more effective against S. aureus, S. pneumoniae, and enterococci than other statins (37)(38)(39)43), while three distinct simvastatin MICs were reported against S. aureus clinical isolates from the United Kingdom and Jordan as well as against typed reference strains (Table 1) (37,38,41,42). It is also noteworthy that, while the MICs of statins varied according to the statin and pathogen tested, the in vitro MICs ranged from circa 15 to 400 mg/liter, far exceeding the range of typical peak plasma concentrations of patients on oral statins, which generally range from circa 10 to 300 g/liter.…”
Section: Effects Of Statins On In Vitro Bacterial Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…30,31 these mechanisms could support a hypothetical effect of statins for prevention of al after colorectal surgery; however, most of the published studies on the pleiotropic effects was conducted in experimental settings other than intestinal anastomosis. therefore, results should be interpreted with caution in relation to al.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, both pravastatin and pitavastatin are interesting candidates for clinical studies of synergy between statins and traditional antifungal drugs. At therapeutic doses, the mean concentrations of statins in human serum are in the nanomolar range [18][19][20][21][22] as shown in TABLE 1.…”
Section: Different Statins and Their Propertiesmentioning
confidence: 99%